Is cannabis neurotoxic for the healthy brain? A meta‐analytical review of structural brain alterations in non‐psychotic users. Issue 7 (30th September 2013) - Rocchetti, Matteo; Crescini, Alessandra; Borgwardt, Stefan; Caverzasi, Edgardo; Politi, Pierluigi; Atakan, Zerrin; Fusar‐Poli, Paolo
Abstract : Aims: Despite growing research in the field of cannabis imaging, mostly in those with a psychotic illness, the possible neurotoxic effects of smoked cannabis on the healthy brain have yet to be fully understood. There appears to be a need to evaluate the existing imaging data on the neuroanatomical effects of cannabis use on non‐psychotic populations. Methods: We conducted a meta‐analytical review to estimate the putative neurotoxic effect of cannabis in non‐psychotic subjects who were using or not using cannabis. We specifically tested the hypothesis that cannabis use can alter grey and white matter in non‐psychotic subjects. Results: Our systematic literature search uncovered 14 studies meeting the inclusion criteria for the meta‐analysis. The overall database comprised 362 users and 365 non‐users. At the level of the individual studies there is limited and contrasting evidence supporting a cannabis‐related alteration on the white and grey matter structures of non‐psychotic cannabis users. However, our meta‐analysis showed a consistent smaller hippocampus in users as compared to non‐users. Heterogeneity across study designs, image acquisition, small sample sizes and limited availability of regions of interest to be included in the meta‐analysis may undermine the core findings of this study. Conclusions: Our results suggest that in the healthy brain, chronic and long‐term cannabis exposure may exert significant effects in brain areas enriched with cannabinoid receptors, such as the hippocampus, which could be related to a neurotoxic action.